2005
DOI: 10.1200/jco.2005.01.109
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity in Melanoma and Anti-Self Responses in a Phase I Trial With the Anti-Cytotoxic T Lymphocyte–Associated Antigen 4 Monoclonal Antibody CP-675,206

Abstract: CP-675,206 can be administered safely to humans as a single IV dose up to 15 mg/kg, resulting in breaking of peripheral immune tolerance to self-tissues and antitumor activity in melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
418
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(436 citation statements)
references
References 29 publications
7
418
2
5
Order By: Relevance
“…Rates of grade 3 or higher diarrhea/colitis in this study were similar to the rates reported in the phase II study of single-agent tremelimumab at a higher dose (15mg/kg). Interestingly, 10mg/kg was the MTD identified in the first-in-human study of tremelimumab 9 and ultimately this dose was found to be more tolerable when dosed at a frequency of every 3 months. 10 We found no evidence that CP-870,893 aggravated tremelimumab-associated toxicity or vice versa, nor did a new spectrum of autoimmunity emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of grade 3 or higher diarrhea/colitis in this study were similar to the rates reported in the phase II study of single-agent tremelimumab at a higher dose (15mg/kg). Interestingly, 10mg/kg was the MTD identified in the first-in-human study of tremelimumab 9 and ultimately this dose was found to be more tolerable when dosed at a frequency of every 3 months. 10 We found no evidence that CP-870,893 aggravated tremelimumab-associated toxicity or vice versa, nor did a new spectrum of autoimmunity emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Limited pre-clinical studies have suggested that aging may result in an imbalanced immune system (between native and adaptive arms) that favors antitumor activity. 29 Clinical trials have confirmed that elderly patients with advanced melanoma do respond to immunotherapies such as tumor vaccines, and anti-CTLA4 therapy 5,30,31 Ipilimumab has shown an improvement in overall survival (OS) in advanced melanoma compared to an experimental peptide vaccine 5 and a 5-y OS of »20%. 32 One subgroup analysis suggested equivalent benefits in patients >70 y.…”
Section: Discussionmentioning
confidence: 99%
“…They are also being used in combination with tumour vaccines (peptides) [9,10] or various forms of chemotherapy (http://clinicaltrials.gov/). Importantly, tumour responses often develop over an extended period of weeks or months and tend to correlate with autoimmune manifestations and systemic inflammation, seen in at least a third of patients [11,12].…”
Section: Introductionmentioning
confidence: 99%